Visitor encounters with the Great Barrier Reef : aesthetics, heritage, and the senses - Pocock, Celmara (Celmara Anne) (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Visitor Encounters with the Great Barrier Reef explores how visitor encounters have shaped the history and heritage of the reef. Moving beyond the visual aesthetic significance, the book highlights the importance of multi-sensual experiences in understanding the region as a UNESCO World Heritage Site. Drawing on archival and ethnographic research, the book describes how visitors have experienced the Great Barrier Reef through personal embodied encounters and the mechanisms they have used to understand, access and share these experiences with others. Illustrating how such experiences contribute to a knowledge of place, Pocock also explores the vital role of reproduction and photography in sharing experiences with those who have never been there. The second part of the book analyses visitor experiences and demonstrates how they underpin three key frames through which the Reef is understood and valued: the islands as paradise, the underwater coral gardens, and the singular Great Barrier Reef. Acknowledging that these constructs are increasingly removed from human experience, Pocock nevertheless demonstrates that they are integral to recognition of the region as a World Heritage Site. Demonstrating how experiences of the Reef have changed over time, Visitor Encounters with the Great Barrier Reef should be of interest to academics and students working in the fields of heritage studies, history and tourism. It should also be of interest to heritage practitioners working around the globe"--
Orientation : wayfinding, cartography and spatial knowledge -- Sensuous encounters : embodied experiences of the Reef -- Transmission of knowledge : taking the Reef to the world -- Reef islands as signifiers of paradise -- Coral gardens : cultivating the underwater -- The Great Barrier Reef.
Revision of author's thesis (doctoral)--James Cook University, 2003, titled Romancing the Reef : history, heritage and the hyper-real.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Anthropological aspects -- Australia -- Great Barrier Reef (Qld.); Natural history -- Australia -- Great Barrier Reef (Qld.); Great Barrier Reef (Qld.) -- History; Great Barrier Reef (Qld.) -- Description and travel; Great Barrier Reef Marine Park (Qld.); SOCIAL SCIENCE / Archaeology